Accuracy of first‐trimester combined test in screening for trisomies 21, 18 and 13. (26th April 2017) - Santorum, M.; Wright, D.; Syngelaki, A.; Karagioti, N.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the diagnostic accuracy of a previously developed model for the first‐trimester combined test in screening for trisomies 21, 18 and 13. Methods: This was a prospective validation study of screening for trisomies 21, 18 and 13 by assessment of a combination of maternal age, fetal nuchal translucency, fetal heart rate and serum free β‐human chorionic gonadotropin (β‐hCG) and pregnancy‐associated plasma protein‐A (PAPP‐A) at 11 + 0 to 13 + 6 weeks' gestation in 108 982 singleton pregnancies undergoing routine care in three maternity hospitals. A previously published algorithm was used to calculate patient‐specific risks for trisomy 21, 18 and 13 in each patient. The detection rate (DR) and false‐positive rate (FPR) at estimated risk cut‐offs from 1 in 2 to 1 in 1000 were determined. The proportions of trisomies detected were compared to their expected values in different risk groups. Results: In the study population, there were 108 112 (99.2%) cases with normal fetal karyotype or birth of a phenotypically normal neonate and 870 (0.8%) cases with abnormal karyotype, including trisomy 21 ( n = 432), trisomy 18 ( n = 166), trisomy 13 ( n = 56), monosomy X ( n = 63), triploidy ( n = 35) or other aneuploidy ( n = 118). The screen‐positive rates, standardized according to the maternal age distribution in England and Wales in 2011, of fetuses with abnormal or normal karyotype were compatible with those predicted from the previous model; at a risk cut‐off of 1 in 100, the FPR was about 4% and the DRs for trisomies 21, 18 and 13 were 90%, 97% and 92%, respectively. There was evidence that the algorithm overestimated risk. This could, to some degree, reflect under‐ascertainment in pregnancies ending in miscarriage or stillbirth. Conclusion: In a prospective validation study, the first‐trimester combined test detected 90%, 97% and 92% of trisomies 21, 18 and 13, respectively, as well as > 95% of cases of monosomy X and triploidies and > 50% of other chromosomal abnormalities, at a FPR of 4%. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.